Energy – Growth Nexus- A Case of South Asian Countries - Hussain, Saddam; Yu, Chunjiao; Wan, Liu (Asian Journal of Economics and Empirical Research, 2021)
The relationship between energy consumption and economic growth is a hot issue in today’s society. This paper aims to empirically verify the relationship between energy consumption and economic growth. This article analyzes the relation of energy consumption with the economic growth taking the case of South Asian countries (Afghanistan, Bangladesh, Bhutan, India, Pakistan, Sri Lanka, and Nepal) along with the macroeconomic determinants that affect the total economic growth – FDI growth, CPI rate and population growth in order to avoid omitted variable bias and misleading results. The time span of this study covers the period of 1980–2019. To examine the significant relation of these determinants and impact of energy consumption on economic growth, In-pooled regression, Fixed-effects, Bidirectional fixed effect, Random-effects, and GLS estimation regression model are used. The estimated results show a positive correlation of energy consumption and all other economic determinants with economic growth except CPI, where there is a negative correlation founded.